PENERAPAN APLIKASI SLiMS 9.0 DALAM MENINGKATKAN PRODUKTIVITAS KERJA PUSTAKAWAN DI MADRASAH ALIYAH NEGERI 02 JOMBANG - Fadila Zannuba Arifah (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2025)
The current development of technology is very rapid and has a significant impact, especially in education in Indonesia. However, the current technological advancements also require education in Indonesia to continuously grow and develop. One form of technological development in educational institutions, particularly in libraries, is the implementation of the SLiMS 9.0 application. In the implementation of the SLiMS 9.0 application, there are also several issues as follows: 1) How is the planning for the implementation of the SLiMS 9.0 application in Madrasah Aliyah Negeri 02 Jombang Library? 2) How is the implementation of the SLiMS 9.0 application in Madrasah Aliyah Negeri 02 Jombang Library? 3) What is the form of librarian work productivity in the implementation of the SLiMS 9.0 application in Madrasah Aliyah Negeri 02 Jombang Library. The method used in this research is qualitative research with data collection through observation, interviews, and documentation. The results of this study are as follows: 1) The planning conducted at the library of Madrasah Aliyah Negeri 02 Jombang consists of five stages, namely goal setting, strategy determination, policies, procedures, and budgeting; 2) The implementation of the SLiMS 9.0 Bulian application in improving librarian work productivity at Madrasah Aliyah Negeri 02 Jombang utilizes various available facilities in the library, both the interface and online features that are related to the SLiMS 9.0 Bulian application; 3) The evaluation of the implementation of the SLiMS 9.0 Bulian application in enhancing librarian work productivity is conducted once a year, specifically in December, and it is a comprehensive evaluation. Keywords: Library, SLiMS 9.0 Bulian application, work productivity.